Optimization of technological transport kits using anylogic simulation modeling environment - M.V. Nemkov; V.V. Poptsov; V.M. Nemkov (Интеллект. Инновации. Инвестиции, 2019)
The article presents a solution to the problem of finding the optimal number of standard sets of technological transport for the Management of oil trunk pipelines in Western Siberia. The main task of the Departments is to make decisions in the process of operation of the pipeline, tank, energy and other facilities included in the complex of pipeline transportation of oil and gas. An important task is to maintain the efficiency of the system of oil trunk pipelines, which requires to have at its disposal its own fleet of technological transport or contact contractors. In this article we will focus on pipeline maintenance on their own. At the same time, to solve equal tasks, namely the maintenance or repair of the main oil pipeline, the Management of the main oil pipeline can have significant differences in the length of the pipelines, their age, natural and climatic conditions, the development of transport infrastructure, the equipment of CTT and CT in the region and the road network. Such an indicator as the age of the pipeline has a significant impact on the formation of the need for technological transport due to the increase or decrease in the number of repairs. In the existing regulations of the equipment of units of technological transport, these factors are not taken into account in full. To solve this problem, the approach to the operation of technological transport was analyzed, as well as a model of simulation of transport service of the oil pipeline system by agent modeling in anylogic environment was developed. This program allows you to adjust the model to the desired conditions, varying the speed of equipment, the number of objects under study, as well as using GIS maps with transport bases and pipelines. The model includes the standard number of pipeline repairs in the year under study, the speed of technological transport, repair time, type of repair, type of technological transport. In this paper, technical transport works teams. On the basis of modeling, it is proposed to determine the real need for a technological TRANS-port for the Management of the oil trunk pipeline, as well as to form adjustments to existing regulations on the need for equipment.